The Vietnam War, the Whale Hunt and the Wall in Linda Hogan's People of the Whale. - Ahokas Pirjo (Sweden, 2022)
Native Americans participated in the Vietnam War in a disproportionally large number in relation to their actual population in the United States. Nevertheless, few American Indian novelists have dealt with the war and its legacy. This article explores the significance of the Vietnam Veterans Memorial and the Pacific Northwest Coast to the protagonist’s war trauma in Linda Hogan’s novel People of the Whale (2008). Drawing upon Michelle Balaev’s pluralistic model of literary trauma theory, my reading of the novel investigates the importance of place and contextual factors vis-à-vis the protagonist’s process of remembrance of the traumatic event. It also looks at the narrative strategies employed in the novel and uses ecological approaches when exploring the meaning of the two sites. Ultimately, the novel not only raises serious moral and political issues concerning the Vietnam War, but it also shows that the places of healing are symbolically linked to one another